Pulmonary Arterial Hypertension Secondary to Ethanol Sclerotherapy for Renal Artery Embolization - Raya Saba; James Davis; Arvind Balavenkataraman; Aibek E. Mirrakhimov; Aram Barbaryan; Shyam Chalise; Nkemakolam Iroegbu (Case Reports in Critical Care)
Pulmonary arterial hypertension (PAH) has been reported as a major complication to consider and promptly manage in the use of ethanol sclerotherapy. Most of the available data on the development of PAH is derived from the use of ethanol for embolization of arteriovenous malformation, but it has been rarely reported in its other fields of application. We describe a case of outpatient renal artery embolization using ethanol, in which respiratory failure develops secondary to PAH despite adhering to safe practice protocols. We highlight the importance of pulmonary arterial pressure monitoring and the treatment steps to follow in order to avoid irreversible fatal outcomes.